Taller: el Valle Inferior de Río Negro y el Valor agregado en origen - Kehler Gonzalez, Juan José; Muzi, Enrique; Alder, Maite; Garcia Cortes, Manuel; Martinez, Roberto Simon (EEA Valle Inferior, INTA, 2024)
EEA Valle Inferior